Peru Public Expenditure Review - World Bank (World Bank, Washington, DC, 2018)
This Public Expenditure Review (PER) was prepared at the request of Peru’s Ministry of Economy and Finance (MEF).The PER offers analysis, options for reform, and measures in selected areas and sectors to achieve efficiency gains and fiscal savings (where possible), while improving (at least not harming) equity. In the context of less favorable external environment, public finance is one of the critical issues that has come to the fore. The gradual fiscal consolidation process initiated offers a unique opportunity to carry out important fiscal and sectoral reforms. Preserve the hard-won gains of sound fiscal policy. This report consists of two parts; Part I focuses on the cross-cutting issues and challenges. The macro-fiscal chapter examines revenue and expenditure trends, provides a fiscal sustainability analysis and an assessment of contingent liabilities. It discusses relevant crosscutting fiscal issues, expenditure rigidities, revenue challenges, and areas to improve the multiannual macroeconomic framework (MMF). The public procurement chapter evaluates procurement practices applied by all government bodies in the budget. It uses the strategic sourcing methodology and data from Peru’s procurement platform which for the purposes of this analysis has been merged with the budget accounting system (SEAF). It identifies significant fiscal savings and efficiency gains, many of which are relatively easy to achieve. Part II identifies areas for efficiency gains and potential fiscal savings in five selected sectors. These sectors include water and sanitation, health, education, citizen security, and transport. They account for a significant share of the budget and represent a substantial share of public service delivery. These chapters provide several approaches and perspectives in looking at technical and allocative efficiency. The PER identifies at least 1.4 percent of GDP in fiscal savings that arise from efficiency reforms and measures across the areas examined.